A vaccine of L2 epitope repeats fused with a modified IgG1 Fc induced cross-neutralizing antibodies and protective immunity against divergent human papillomavirus types. - Xue Chen; Hongyang Liu; Ting Zhang; Yanchun Liu; Xixiu Xie; Zhirong Wang; Xuemei Xu (PLoS ONE, 2014)
Current human papillomavirus (HPV) major capsid protein L1 virus-like particles (VLPs)-based vaccines in clinic induce strong HPV type-specific neutralizing antibody responses. To develop pan-HPV vaccines, here, we show that the fusion protein E3R4 consisting of three repeats of HPV16 L2 aa 17-36 epitope (E3) and a modified human IgG1 Fc scaffold (R4) induces cross-neutralizing antibodies and protective immunity against divergent HPV types. E3R4 was expressed as a secreted protein in baculovirus expression system and could be simply purified by one step Protein A affinity chromatography with the purity above 90%. Vaccination of E3R4 formulated with Freunds adjuvant not only induced cross-neutralizing antibodies against HPV pseudovirus types 16, 18, 45, 52, 58, 6, 11 and 5 in mice, but also protected mice against vaginal challenges with HPV pseudovirus types 16, 45, 52, 58, 11 and 5 for at least eleven months after the first immunization. Moreover, vaccination of E3R4 formulated with FDA approved adjuvant alum plus monophosphoryl lipid A also induced cross-neutralizing antibodies against HPV types 16, 18 and 6 in rabbits. Thus, our results demonstrate that delivery of L2 antigen as a modified Fc-fusion protein may facilitate pan-HPV vaccine development.